Nucleic Acid Therapy for β-Thalassemia - d'Arqom A (Dove Medical Press, 2020)
Annette d’Arqom1,2 1Graduate Program in Molecular Medicine, Faculty of Science, Mahidol University, Bangkok, Thailand; 2Department of Pharmacology and Therapy, Faculty of Medicine, Universitas Airlangga, Surabaya, IndonesiaCorrespondence: Annette d’Arqom Department of Pharmacology and Therapy, Faculty of MedicineUniversitas Airlangga, Jl. Mayjen Prof. Dr. Moestopo 47, Surabaya 60131, East Java, IndonesiaEmail annette-d-a@fk.unair.ac.idAbstract: β-thalassemia is caused by mutations in the β-globin gene which diminishes or abolishes β-globin chain production. This reduction causes an imbalance of the α/β-globin chain ratio and contributes to the pathogenesis of the disease. Several approaches to reduce the imbalance of the α/β ratio using several nucleic acid-based technologies such as RNAi, lentiviral mediated gene therapy, splice switching oligonucleotides (SSOs) and gene editing technology have been investigated extensively. These approaches aim to reduce excess free α-globin, either by reducing the α-globin chain, restoring β-globin expression and reactivating γ-globin expression, leading a reduced disease severity, treatment necessity, treatment interval, and disease complications, thus, increasing the life quality of the patients and alleviating economic burden. Therefore, nucleic acid-based therapy might become a potential targeted therapy for β-thalassemia.Keywords: RNAi, splice switching oligonucleotides, gene editing, targeted therapy, good health and well-being